ANALISIS PERAWATAN DAN KESELAMATAN KAPAL TERHADAP KESEJAHTERAAN NELAYAN - Wahyuni, Eni Tri; Rubiyanto, Aan; Widodo, B.L Hentri (UNIMAR AMNI Semarang, 2024)
Fishermen's lives are less prosperous, this is due to uncertain income and operational costs in shipping and ship maintenance. The aim of this research is to analyze the welfare of fishermen in Gempol Sewu Village, Kec. Rowosari, Kendal Regency. The method used in this research is a qualitative method, with this qualitative method you can find out directly what things influence the income and welfare of fishermen by conducting interviews with fishermen in the Gempol Sewu area. The information in thisresearch is fishermen in Gempol Sewu Village who are represented by several fishermen in the area. Based on interviews and literature studies conducted, it can be concluded that the lack of welfare of fishermen is caused by several main factors. First of all, the cost of boat maintenance and safety while sailing are crucial factors that put financial pressure on fishermen. Efforts to ensure vessels remain in good condition andmaintain safety while sailing require significant investment, which may be difficult for most fishermen to afford. Concrete steps such as providing skills training programs, easy access to capital at low interest rates, and the formation of fishermen's cooperatives can be a solution to improve the welfare of fishermen and open up opportunities for them to develop businesses other than being fishermen. In this way, it is hoped that fishermen can have a more economically sustainable alternative and improve their overall standard of living.